What issues prevent the development of sustainable food value chains for Albanian traditional mountains products? - Bombaj F. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
The Albanian mountainous areas have local products with strong link to their specific origin. The current dynamics of the milk and meat value chains shows an asymmetric power that is hold by the dairies and the middlemen. The aim of this paper is to analyse what issues prevent the development of sustainable value chains for traditional mountains products. The use of a comparative analysis between the milk and meat value chain of a mountain territory is been made by analysing the strengths and weaknesses of the considered territory. The analysis is based on three stages: (1) analysis on the national milk and meat value chain; (2) analysis of the local livestock products value chain of the considered territory; (3) discussion and conclusion. Results shows that the current development of the milk and meat value chain does not position the local products in a niche market capable of engaging a virtuous circle for a good remuneration of the producers. This situation is not favourable for the development of mountainous products with specific characteristics and high reputation.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)